Total Hyptolide of Indonesian Hyptis pectinata extracts in a various solvent using HPLC and UV-Vis spectroscopy and their toxicities - Meiny Suzery; Siti Khumairoh; Bambang Cahyono (Jurnal Kimia Sains dan Aplikasi, 2019)
The bioactive compound of hyptolide has been isolated from an Indonesian plant Hyptis pectinata using various solvents. The pure compound was then used as a standard in quantitative analysis using HPLC and UV-Vis spectroscopy in ethanol (EEth), ethyl acetate (EEa), acetone (Eac) and hexane (Ehex) extract each earned 3.14%, 0.01%, 1.33% and 0.04% (dry weight per sample). The standard curve of hyptolide using UV spectroscopy has been obtained with the coefficient of relationship (r) of 0.997. However, the use of spectroscopy was not recommended for the standardization of hyptolide in the extract due to interference from other compounds that absorb the same wavelength. Furthermore, the toxicity test using the Brine Shrimp lethality test shows LC50 value of 92-181 ppm, which was in EEa compared to EEth, Eac, and Ehex.